Usage of the BB84 Protocol for Communications in Pairs of Orbiting Satellites - Nieto-Chaupis, Huber (2019)
We use the scheme of the BB84 protocol to estimate the Bit Error Rate (BER) between two satellites under the action of exchanging wireless communication inside the framework of the Internet of Space Things. The usage of the Bessel basis yields oscillations of BER curves.